Correlations of Serum and Urine Levels of Neopterin, IL-8, IL-6, IL-6R, Basic Fetoprotein and Hepatocytes Growth Factor with Acute Rejection in kidney Transplantation - Miki Tsuneharu (Pteridines, 1998)
Levels of serum- and urinary-neopterin and serum-IL-6 and IL-6R of kidney transplant recipients "Were higher in acute rejection episode than in stable condition. IL-8 serum levels had risen prior to clinical diagnosis of acute rejection episode. Serum HGF levels also increased during acute rejection episode to over 1 ng/ml. Serum-neopterin and IL-6R levels were relatively sensitive for the detection of acute rejection episode.